Redistributive income taxation under outsourcing and foreign direct investment - Thomas Aronsson; Erkki Koskela (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper deals with optimal income taxation under labor outsourcing and FDI. We show how the optimal income tax response to the joint effect of outsourcing and FDI depends on whether FDI is complementary with, or substitutable for, domestic labor.
Keywords: D60; H21; H23; H25; J31; 330; outsourcing; foreign direct investment; optimal nonlinear taxation; Outsourcing; Offshoring; Direktinvestition; Einkommensteuer; Optimale Besteuerung; Lohnstruktur; Einkommensumverteilung; Theorie